Efeito da fadiga no andar de pacientes com doença de Parkinson: relação com o nível de atividade física - Santos, Paulo Cezar Rocha dos [UNESP] (2013)
The symptom of fatigue and the muscle fatigue are both considered as problems that can attack patients with Parkinson disease (PD), which can have influence on gait. Physical activity counteracts the commitments of the PD and the effects of fatigue. However, the relationship between the level of physical activity and the fatigue in patients compared to individuals without PD is not very clear as well as the influence of induced fatigue on gait parameters in regular room and on the floor with overdrive obstacle PD patients. To fill these gaps 3 studies were proposed: Study 1 that aims to relate the symptom of fatigue with physical activity level in patients with PD and in individuals not affected by PD as to compare the perception of fatigue between these two groups. This study was composed by the participation of 80 individuals, in which 40 were patients with PD and 40 were patients without the disease (group control). Participants, within their groups, were divided into active (20) and inactive (20) according to the Baecke Questionnaire that was modified for the elderly. The Multidimensional Fatigue Inventory was used to verify the subjective perception of fatigue in both groups. Two-way ANOVA was used to compare groups according to the levels of physical activity and the Pearson correlation test that was performed to verify the relationship between physical activity level and subjective perception of fatigue for each group. There was only one difference which was between the fatigue of the participants with PD compared with controls without effect on physical activity level. Still, there was no relationship between level of physical activity and perception of fatigue. Patients with PD have a higher perception about the symptom of fatigue on overall dimensions, physical, low motivation, mental and reduced level of physical activity, when compared with the control individuals; Study 2 and 3 aim to analyze the effect of muscle fatigue on...